THE EFFECT OF GROUP GUIDANCE USING INDIRECT MODELING TECHNIQUES BASED ON SHORT FILMS TO INCREASE AWARENESS OF THE RISKS OF EARLY MARRIAGE - Muhammad Husni; Abdullah Pandang; Sahril Buchori (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to determine the effect of group counseling using the indirect modeling technique based on short films to increase awareness of the risks of early marriage among adolescents. The research method used is quantitative with a one-group pretest-posttest design. The subjects of this study were junior high school students who showed low awareness regarding the negative impacts of early marriage. The intervention was conducted through several group counseling sessions, where students were shown short films containing moral messages and real-life situations that reflect the adverse effects of early marriage. The data were analyzed using descriptive statistics and t-tests to determine the significance of change before and after the intervention. The findings indicate a significant increase in students’ awareness after participating in the group counseling. The use of short films in indirect modeling proved effective in helping students develop empathy, better understand the long-term risks of early marriage, and reflect on their own values and decisions. This study concludes that the implementation of group counseling with short-film-based indirect modeling techniques is an effective alternative approach to increase adolescents’ awareness about the risks of early marriage. The results have implications for guidance and counseling services in schools as a preventive measure to reduce the trend of early marriage among teenagers.